Knowledge in Sustainable Development Goals of Teacher Education Students in Isabela State University - Jimenez, Joshua; Babaran, Nilda (International Journal of Arts, Sciences and Education, 2024)
This study was conducted to determine the extent of knowledge in Sustainable Development Goals (SDGs) of teacher education students in Isabela State University. The study also sought if teacher education students’ knowledge of SDGs is different based on their sex, field of specialization, and year level. The study adopted a survey research methodology to determine students’ knowledge of SDGs. Respondents consisted of three-hundred sixty-one (361) teacher education students across selected campuses of Isabela State University. Descriptive statistics showed the respondents have high knowledge in SDGs. Using T-test and F-test, results revealed that there is no significant difference in their knowledge of SDGs between sexes. Between their field of specializations and year levels, differences in their knowledge are significant. Findings suggest that need to strengthen the integration of SDG-content into all fields of specialization under the teacher education program and the need set up mentorship programs and opportunities where the seniors can help guide the juniors in understanding the concepts of SDGs.